Efficacy and Safety of Opinercept Tumor Necrosis Factor Inhibitor Therapy for Drug-Refractory Rheumatoid Arthritis: A Randomized Clinical Trial - Toong-Hua LIANG,; Chyou-Shen LEE,; Shinn-Shing LEE,; Chien-Sheng WU,; Kun-Hung CHEN,; Ping-Ning HSU,; Hsiao-Yi LIN, (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate the efficacy and safety profile of opinercept for rheumatoid arthritis (RA) patients undergoing disease- modifying anti-rheumatic drugs (DMARDs) therapy. Patients and methods: A total of 98 patients with active RA (17 males, 81 females; mean age 58.6±12.2 years; range, 24.3 to 85.3 years) were randomized into opinercept plus DMARDs (OD group) or placebo plus DMARDs (PD group), in a 24-week treatment period. Primary outcome was American College of Rheumatology score (ACR20) at week 24. Other exploratory endpoints included ACR50, ACR70 and disease activity score-28 (DAS28) at week 12 and 24, tender/swollen joint counts, pain, Health Assessment Questionnaire-Disability Index, erythrocyte sedimentation rate, and C-reactive protein level. Incidence of adverse events (AEs), vital signs and physical findings, and laboratory test results were also evaluated. Results: Patients in OD group showed significantly higher achievement percentage of ACR20 at week 24 than the PD group (76.6% vs. 30.3%, p<0.001). The evaluation of DAS28 was significantly improved in OD patients compared to PD patients at weeks 12 and 24. Most of the occurred AEs were mild or moderate and considered unrelated to study treatments. Conclusion: Opinercept concurrent with DMARDs was superior to DMARDs alone in slowing RA progression and ameliorating symptoms, with well- tolerated and acceptable safety profile.